Matrix-modified SiC / SiC composite material and preparation method thereof
By depositing the SIC layer on the surface of the B4C powder and the method of bombardment of ionics, combined with multiple pressure impregnation and high temperature treatment, the problem of insufficient the performance of traditional SIC/SIC composite materials has significantly improved its toughness, mechanical performance, and reusable use. performance.
Patent Information
- Application Number
- CN202411486679.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-23
AI Technical Summary
Traditional SiC/SiC composite materials are difficult to meet the requirements of strength, toughness, high temperature resistance, oxidation resistance and reusable performance in aerospace vehicle structural parts. In particular, the modification method of the matrix cannot effectively improve its mechanical properties and reusable performance. performance.
Through the chemical gas sedimentation method, the SIC layer is deposited on the surface of the B4C powder to form a nuclear shell structure powder, and an ions bombardment in a vacuum environment is performed. High -temperature treatment, combined with pulp immersion process, impregnated and soluble cracking process, and sintering process, and the SIC/SIC composite material of the substrate modification is made.
Significantly improves the toughness, mechanical properties and reusability performance of SiC/SiC composite materials in high-temperature and high-pressure air environments, and extends their creep life in high-temperature and high-pressure air environments.
Smart Images

Figure BDA0005098886280000131
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aerospace materials, and in particular relates to a matrix-modified SiC / SiC composite material and a preparation method thereof. Background Art
[0002] The structural parts of aerospace vehicles have increasing requirements for the strength, toughness, high temperature resistance, oxidation resistance and reusability of SiC / SiC composites. Traditional SiC / SiC composites that rely solely on SiC matrix are difficult to meet the requirements, and the SiC matrix needs to be boron-modified to improve its reusability. Conventional matrix boron modification methods often have limited improvements in its mechanical properties and reusability, so it is urgent to develop a preparation method that can comprehensively and effectively improve the mechanical properties, high temperature resistance, oxidation resistance and / or reusability of SiC / SiC composites.
[0003] In summary, it is very necessary to provide a matrix-modified SiC / SiC composite material and a preparation method thereof. Summary of the invention
[0004] In order to solve one or more technical problems existing in the prior art, the present invention provides a matrix-modified SiC / SiC composite material and a preparation method thereof.
[0005] In a first aspect, the present invention provides a method for preparing a matrix-modified SiC / SiC composite material, the method comprising the following steps:
[0006] (1) depositing a SiC layer on the surface of B4C powder by chemical vapor deposition to obtain a core-shell structure powder;
[0007] (2) bombarding the core-shell structure powder with argon ions under a vacuum environment, and then adding the bombarded core-shell structure powder into an ammonium polyacrylate dispersant to disperse it evenly to obtain a modified liquid;
[0008] (3) using a modified liquid to perform multiple pressure impregnations on the SiC fiber preform having the interface layer, and then subjecting the preform to high temperature treatment to obtain a modified SiC fiber preform;
[0009] (4) The modified SiC fiber preform is subjected to multiple rounds of impregnation, curing and cracking with a liquid polycarbosilane precursor, and then subjected to high-temperature sintering in an inert atmosphere to obtain a matrix-modified SiC / SiC composite material.
[0010] Preferably, the particle size of the B4C powder is 500nm-1μm, and the thickness of the SiC layer is 250nm-500nm.
[0011] Preferably, when bombardment is performed by argon ions in a vacuum environment, the vacuum pressure is 10-5 mbar, the voltage during the bombardment process is 1.0-2.0 keV, the current is 3-9 mA, and the bombardment time is 5-15 min.
[0012] Preferably, the volume fraction of the ammonium polyacrylate dispersant in the modified liquid is 50 to 70 vol.%.
[0013] Preferably, in step (3), 5 to 10 pressure impregnations are performed; preferably, the pressure of each pressure impregnation is 0.1 to 0.5 MPa, and the time of each pressure impregnation is 5 to 10 minutes.
[0014] Preferably, in step (3), the temperature of the high temperature treatment is 400-600° C., preferably 500° C., and the time of the high temperature treatment is 0.5-2 h.
[0015] Preferably, in step (4), 2 to 6 rounds of impregnation, curing and cracking are performed; during each round of impregnation, curing and cracking, the impregnation is vacuum impregnation, the vacuum impregnation pressure is 100 to 500 Pa, the vacuum impregnation time is 0.5 to 2 h, the curing temperature is 200 to 400°C, the curing time is 0.5 to 1 h, the cracking temperature is 900 to 1200°C, and the cracking time is 1 to 2 h.
[0016] Preferably, the temperature of the high temperature sintering is 1200-1400° C., preferably 1300° C., and the time of the high temperature sintering is 0.5-1.5 h.
[0017] Preferably, the SiC fiber preform having an interface layer is a SiC fiber preform having a PyC interface layer.
[0018] In a second aspect, the present invention provides a matrix-modified SiC / SiC composite material prepared by the preparation method described in the first aspect of the present invention.
[0019] Compared with the prior art, the present invention has at least the following beneficial effects:
[0020] (1) The present invention improves the stability of the matrix structure of the SiC / SiC composite material by accurately constructing the SiC / B4C core-shell structure, and effectively improves the toughness of the SiC / SiC composite material; and, the present invention can construct a channel for the release of B4C at high temperature by depositing a SiC layer on the outside of the B4C particles and assisting with argon ion bombardment, and after argon ion bombardment, it also helps the sintering of the matrix, which is beneficial to improving the reusability of the material and effectively improving the creep life of the SiC / SiC composite material in a high temperature and high pressure air environment.
[0021] (2) The present invention combines the slurry impregnation process, the impregnation solidification cracking process and the sintering process to quickly strengthen the sintering of each component in the SiC / SiC composite material matrix, and effectively improves the mechanical properties of the SiC / SiC composite material. DETAILED DESCRIPTION
[0022] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0023] In a first aspect, the present invention provides a method for preparing a matrix-modified SiC / SiC composite material, the method comprising the following steps:
[0024] (1) depositing a SiC (silicon carbide) layer on the surface of B4C (boron carbide) powder by chemical vapor deposition to obtain a core-shell structure powder (also referred to as SiC / B4C core-shell structure powder); the present invention does not specifically limit the process conditions of the chemical vapor deposition method in step (1), and those skilled in the art can routinely select;
[0025] (2) bombarding the core-shell structure powder with argon ions under a vacuum environment, and then adding the bombarded core-shell structure powder into a polyammonium acrylate dispersant (ammonium polyacrylate) to disperse it evenly to obtain a modified liquid; the present invention does not specifically limit the source of the ammonium polyacrylate dispersant, and the ammonium polyacrylate that can be directly purchased or synthesized by an existing method can be used;
[0026] (3) using a modifying liquid to perform multiple pressure impregnations on the SiC fiber preform having the interface layer, and then subjecting it to high temperature treatment under an inert atmosphere to obtain a modified SiC fiber preform (which may also be referred to as a modified SiC composite material); during the pressure impregnation in step (3), the SiC fiber preform having the interface layer can be completely immersed in the modifying liquid;
[0027] (4) A modified SiC fiber preform is subjected to multiple rounds of impregnation, curing and cracking using a liquid polycarbosilane precursor (i.e., liquid polycarbosilane), and then subjected to high-temperature sintering under an inert atmosphere to obtain a matrix-modified SiC / SiC composite material. The present invention does not specifically limit the liquid polycarbosilane, and a product that can be directly purchased or a product synthesized by an existing method can be used. In this step (4), the modified SiC fiber preform can be completely immersed in the liquid polycarbosilane precursor.
[0028] The present invention improves the stability of the matrix structure of the SiC / SiC composite material through the precise construction of the SiC / B4C core-shell structure, and effectively improves the toughness of the SiC / SiC composite material; the present invention finds that the core-shell structure powder obtained by depositing the SiC layer on the surface of the B4C powder is significantly helpful to improve the toughness, mechanical properties and reusability of the SiC / SiC composite material in a high-temperature and high-pressure air environment compared with depositing the B4C layer on the surface of the SiC powder. This is because when the SiC layer is deposited on the surface of the B4C to form a core-shell structure, the SiC layer can better buffer thermal stress, reduce cracking or peeling caused by differences in thermal expansion coefficients in a high-temperature and high-pressure air environment, and improve the high-temperature stability and reusability of the material. When SiC covers the surface of the B4C particles, the formed core-shell structure can better stabilize the structure of the B4C and prevent it from undergoing excessive oxidation reaction in a high-temperature environment. This core-shell structure can effectively disperse and relieve stress, improve the overall mechanical strength and toughness of the SiC / SiC composite material, and SiC and B4C have good interface bonding. The SiC outer layer in the core-shell structure can effectively enhance the bonding between particles and with the matrix material. In addition, the present invention can construct a channel for releasing B4C at high temperature by depositing a SiC layer on the outside of the B4C particles and assisting with argon ion bombardment, and it can also help the sintering of the matrix after argon ion bombardment, which is beneficial to improving the reusability of the material and effectively improving the creep life of the SiC / SiC composite material in a high-temperature and high-pressure air environment. The present invention can construct a microscopic channel by depositing a layer of SiC on the outside of the B4C particles and assisting with argon ion bombardment to facilitate the escape of B4C release products, which is beneficial to improving the reusability of the material at high temperature. The SiC layer has good high-temperature resistance and oxidation resistance. The protective layer it forms on the surface of B4C can effectively reduce the occurrence of oxidation or decomposition reactions at high temperatures. Through argon ion bombardment, tiny channels are formed on the SiC layer, which can release the carbonized gas and / or other volatile products generated in the B4C at high temperature, reduce the accumulation of internal pressure, and reduce the possibility of cracking or structural damage of the material during thermal cycling, so that the material can perform more stably in a high-temperature and high-pressure air environment and extend its service life. The present invention combines the slurry impregnation process, the impregnation solidification cracking process and the sintering process to quickly strengthen the sintering of each component in the SiC / SiC composite material matrix, and effectively improves the mechanical properties of the SiC / SiC composite material.
[0029] According to some preferred embodiments, the particle size (average particle size) of the B4C powder is 500nm to 1μm (e.g., 500nm, 600nm, 700nm, 800nm, 900nm or 1μm), and the thickness (average thickness) of the SiC layer is 250nm to 500nm (e.g., 250, 300, 350, 400, 450 or 500nm).
[0030] According to some preferred embodiments, when bombardment is performed by argon ions in a vacuum environment, the vacuum pressure is 10 - 5 mbar or less, the voltage during the bombardment process is 1.0-2.0 keV, the current is 3-9 mA, and the bombardment duration (bombardment time) is 5-15 min. In the present invention, it is preferred that the voltage during the bombardment process is controlled to be 1.0-2.0 keV, the current is 3-9 mA, and the bombardment time is 5-15 min, which is conducive to effectively constructing a reasonable and stable channel for B4C release at high temperature, thereby helping to improve the overall performance of the obtained matrix-modified SiC / SiC composite material; the present invention finds that if the voltage and current during the bombardment process are too large and the bombardment time is too long, it will cause excessive bombardment of the SiC layer, which will make the SiC layer too thin or even have holes, weakening its protective effect, and excessive bombardment may cause the structure of the release channel to deform, resulting in irregular or failed channels released at high temperatures, affecting the release function, and if the voltage and current during the bombardment process are too small and the bombardment time is too short, the bombardment effect will be insufficient, which is not conducive to forming an effective release channel on the SiC layer, which will affect the performance of the SiC / SiC composite material.
[0031] According to some preferred embodiments, the volume fraction of the ammonium polyacrylate dispersant in the modified liquid is 50 to 70 vol.% (eg, 50, 55, 60, 65 or 70 vol.%).
[0032] According to some preferred embodiments, in step (3), pressure impregnation is performed 5 to 10 times (for example, 5, 6, 7, 8, 9 or 10 times); preferably, the pressure of each pressure impregnation is 0.1 to 0.5 MPa (for example, 0.1, 0.2, 0.3, 0.4 or 0.5 MPa), and the time of each pressure impregnation is 5 to 10 min (for example, 5, 6, 7, 8, 9 or 10 min).
[0033] According to some preferred embodiments, in step (3), the temperature of the high temperature treatment is 400-600°C (e.g., 400°C, 450°C, 500°C, 550°C or 600°C), preferably 500°C, and the time of the high temperature treatment is 0.5-2h.
[0034] According to some preferred embodiments, in step (4), 2 to 6 rounds (e.g., 2, 3, 4, 5 or 6 rounds) of impregnation, curing and cracking are performed; during each round of impregnation, curing and cracking, the impregnation is vacuum impregnation, the pressure of the vacuum impregnation is 100 to 500 Pa (e.g., 100, 200, 300, 400 or 500 Pa), the time of the vacuum impregnation is 0.5 to 2 h (e.g., 0.5, 1, 1.5 or 2 h), the temperature of the curing is 200 to 400 ° C (e.g., 200 ° C, 250 ° C, 300 ° C, 350 ° C) 0°C or 400°C), the curing pressure is 1-4MPa (e.g., 1MPa, 2MPa, 3MPa or 4MPa), the curing time is 0.5-1h (e.g., 0.5 or 1h), the cracking temperature is 900-1200°C (e.g., 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C or 1200°C), and the cracking time is 1-2h (e.g., 1, 1.5 or 2h); in the present invention, the cracking is carried out under an inert atmosphere, and the cracking is normal pressure cracking.
[0035] According to some preferred embodiments, the high temperature sintering temperature is 1200-1400°C (for example, 1200°C, 1250°C, 1300°C, 1350°C or 1400°C), preferably 1300°C, and the high temperature sintering time is 0.5-1.5h (for example, 0.5, 1 or 1.5h); in the present invention, the high temperature sintering is carried out under normal pressure.
[0036] According to some preferred embodiments, the SiC fiber preform with an interface layer is a SiC fiber preform with a PyC interface layer; in the present invention, the thickness (average thickness) of the PyC interface layer is, for example, 100 to 300 nm; in the present invention, the SiC fiber preform is preferably a third-generation SiC fiber preform, that is, a fiber preform formed using third-generation SiC fibers; in the present invention, a PyC interface layer (pyrolytic carbon interface layer) can be deposited on the surface of the SiC fiber preform by chemical vapor deposition, which is a conventional technology in the art.
[0037] In the second aspect, the present invention provides a matrix-modified SiC / SiC composite material prepared by the preparation method described in the first aspect of the present invention; the SiC / SiC composite material prepared by the present invention has excellent high temperature resistance, oxidation resistance, and reusability, and can be used for high-performance complex structural parts.
[0038] The present invention will be further described below by way of examples, but the protection scope of the present invention is not limited to these embodiments. The present invention may also have other various embodiments. Without departing from the spirit and essence of the present invention, those skilled in the art may make various corresponding changes and deformations according to the present invention, but these corresponding changes and deformations shall all belong to the protection scope of the claims attached to the present invention. The experimental methods used in the following examples and comparative examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples and comparative examples, unless otherwise specified, can all be obtained from commercial channels.
[0039] Example 1
[0040] ① Preparation of core-shell structure powder: SiC layer is deposited on the surface of B4C powder by chemical deposition process (chemical vapor deposition method) to form core-shell structure powder. The particle size of B4C powder is 500nm and the thickness of SiC layer is 250nm. The core-shell structure powder is bombarded by argon ions in a vacuum environment. During the bombardment, the vacuum pressure is 10 -7 mbar, the voltage during the bombardment was 1.5 keV, the current was 6 mA, and the duration was 10 min, and the bombarded core-shell structure powder was obtained.
[0041] ② Core-shell structure powder dispersion: The bombarded core-shell structure powder is uniformly dispersed in an ammonium polyacrylate dispersant (ammonium polyacrylate) to obtain a modified liquid, wherein the volume fraction of the ammonium polyacrylate dispersant in the modified liquid is 60 vol.%; the obtained modified liquid is used to perform 6 pressure impregnations on a third-generation SiC fiber preform having a PyC interface layer (PyC interface layer with a thickness of 200 nm), and then subjected to high-temperature treatment at 500°C in an inert atmosphere (argon) for 1 hour to obtain a modified SiC fiber preform; wherein the pressure of each pressure impregnation is 0.3 MPa, and the time of each pressure impregnation is 10 min.
[0042] ③ Impregnation, curing and cracking: Use liquid polycarbosilane to carry out 3 rounds of impregnation, curing and cracking process on the modified SiC fiber preform obtained in step ②. In each round of impregnation, curing and cracking process, the impregnation adopted is vacuum impregnation, the vacuum pressure is 100 Pa, the vacuum impregnation time is 1 h, the curing temperature is 300 ° C, the curing time is 1 h, the curing pressure is 2 MPa, the cracking temperature is 1000 ° C, the cracking time is 1 h, and the cracking is carried out under an inert atmosphere (argon).
[0043] ④ High temperature sintering: The composite material after impregnation, curing and cracking in step ③ is subjected to high temperature sintering in an Ar (argon) atmosphere, the high temperature sintering temperature is 1300° C., and the high temperature sintering time is 1 hour to obtain a matrix-modified SiC / SiC composite material.
[0044] The performance test of the matrix-modified SiC / SiC composite material prepared in this embodiment was carried out, and the room temperature fracture toughness was measured to be 20.9 MPa·m 0.5 The room temperature flexural strength is 520MPa, and the creep life in an air environment of 1300℃ and 120MPa reaches 110h.
[0045] Example 2
[0046] Embodiment 2 is substantially the same as Embodiment 1, except that:
[0047] ① Preparation of core-shell structure powder: SiC layer is deposited on the surface of B4C powder by chemical deposition process (chemical vapor deposition method) to form core-shell structure powder. The particle size of B4C powder is 500nm and the thickness of SiC layer is 250nm. The core-shell structure powder is bombarded by argon ions in a vacuum environment. During the bombardment, the vacuum pressure is 10 -7 mbar, the voltage during the bombardment was 0.5 keV, the current was 3 mA, and the duration was 3 min, and the bombarded core-shell structure powder was obtained.
[0048] The performance test of the matrix-modified SiC / SiC composite material prepared in this embodiment was carried out, and the room temperature fracture toughness was measured to be 18.1 MPa·m 0.5 The room temperature flexural strength is 460MPa, and the creep life in an air environment of 1300℃ and 120MPa reaches 93h.
[0049] Example 3
[0050] Embodiment 3 is substantially the same as Embodiment 1, except that:
[0051] ① Preparation of core-shell structure powder: SiC layer is deposited on the surface of B4C powder by chemical deposition process (chemical vapor deposition method) to form core-shell structure powder. The particle size of B4C powder is 500nm and the thickness of SiC layer is 250nm. The core-shell structure powder is bombarded by argon ions in a vacuum environment. During the bombardment, the vacuum pressure is 10 -7 mbar, the voltage during the bombardment was 3 keV, the current was 10 mA, and the duration was 20 min, and the bombarded core-shell structure powder was obtained.
[0052] The performance test of the matrix-modified SiC / SiC composite material prepared in this embodiment was carried out, and the room temperature fracture toughness was measured to be 15.8 MPa·m 0.5 The room temperature flexural strength is 396MPa, and the creep life in an air environment of 1300℃ and 120MPa reaches 84h.
[0053] Comparative Example 1
[0054] ① Impregnation, curing and cracking: Liquid polycarbosilane was used to perform three rounds of impregnation, curing and cracking processes on the third-generation SiC fiber preform with a PyC interface layer (PyC interface layer with a thickness of 200 nm). In each round of impregnation, curing and cracking process, the impregnation was vacuum impregnation with a vacuum pressure of 100 Pa, a vacuum impregnation time of 1 h, a curing temperature of 300 ° C, a curing time of 1 h, a curing pressure of 2 MPa, a cracking temperature of 1000 ° C, a cracking time of 1 h, and the cracking was carried out under an inert atmosphere (argon).
[0055] ② High temperature sintering: The composite material after impregnation, curing and cracking in step ① is subjected to high temperature sintering in an Ar (argon) atmosphere, the high temperature sintering temperature is 1300° C., and the high temperature sintering time is 1 hour to obtain a SiC / SiC composite material.
[0056] The performance test of the SiC / SiC composite material prepared in this comparative example showed that the room temperature fracture toughness was 14.4 MPa·m 0.5 The room temperature flexural strength is 371MPa, and the creep life in an air environment of 1300℃ and 120MPa is 74h.
[0057] Comparative Example 2
[0058] ① Preparation of core-shell structure powder: SiC layer is deposited on the surface of B4C powder by chemical deposition process (chemical vapor deposition method) to form core-shell structure powder. The particle size of B4C powder is 500nm and the thickness of SiC layer is 250nm. The core-shell structure powder is bombarded by argon ions in a vacuum environment. During the bombardment, the vacuum pressure is 10 -7 mbar, the voltage during the bombardment was 1.5 keV, the current was 6 mA, and the duration was 10 min, and the bombarded core-shell structure powder was obtained.
[0059] ② Core-shell structure powder dispersion: The bombarded core-shell structure powder is uniformly dispersed in an ammonium polyacrylate dispersant to obtain a modified liquid, wherein the volume fraction of the ammonium polyacrylate dispersant in the modified liquid is 60 vol.%; the obtained modified liquid is used to perform 6 pressure impregnations on a third-generation SiC fiber preform having a PyC interface layer (PyC interface layer with a thickness of 200 nm), and then subjected to high-temperature treatment at 500°C in an inert atmosphere (argon) for 1 h to obtain a modified SiC fiber preform; wherein the pressure of each pressure impregnation is 0.3 MPa, and the time of each pressure impregnation is 10 min.
[0060] ③ High temperature sintering: The modified SiC fiber preform obtained in step ② is subjected to high temperature sintering in an Ar (argon) atmosphere, the high temperature sintering temperature is 1300° C., and the high temperature sintering time is 1 h to obtain a composite material.
[0061] The performance test of the composite material prepared in this comparative example showed that the room temperature fracture toughness was 12.3 MPa·m 0.5 The room temperature flexural strength is 359MPa, and the creep life in an air environment of 1300℃ and 120MPa is 64h.
[0062] Comparative Example 3
[0063] ① Preparation of core-shell structure powder: SiC layer is deposited on the surface of B4C powder by chemical deposition process (chemical vapor deposition method) to form core-shell structure powder. The particle size of B4C powder is 500nm and the thickness of SiC layer is 250nm. The core-shell structure powder is bombarded by argon ions in a vacuum environment. During the bombardment, the vacuum pressure is 10 -7 mbar, the voltage during the bombardment was 1.5 keV, the current was 6 mA, and the duration was 10 min, and the bombarded core-shell structure powder was obtained.
[0064] ② Core-shell structure powder dispersion: The bombarded core-shell structure powder is uniformly dispersed in an ammonium polyacrylate dispersant to obtain a modified liquid, wherein the volume fraction of the ammonium polyacrylate dispersant in the modified liquid is 60 vol.%; the obtained modified liquid is used to perform 6 pressure impregnations on a third-generation SiC fiber preform having a PyC interface layer (PyC interface layer with a thickness of 200 nm), and then subjected to high-temperature treatment at 500°C in an inert atmosphere (argon) for 1 h to obtain a modified SiC fiber preform; wherein the pressure of each pressure impregnation is 0.3 MPa, and the time of each pressure impregnation is 10 min.
[0065] ③ Impregnation, curing and cracking: Use liquid polycarbosilane to carry out 3 rounds of impregnation, curing and cracking process on the modified SiC fiber preform obtained in step ②. In each round of impregnation, curing and cracking process, the impregnation adopted is vacuum impregnation, the vacuum pressure is 100 Pa, the vacuum impregnation time is 1 h, the curing temperature is 300 ° C, the curing time is 1 h, the curing pressure is 2 MPa, the cracking temperature is 1000 ° C, the cracking time is 1 h, and the cracking is carried out under an inert atmosphere (argon) to obtain a SiC / SiC composite material.
[0066] The performance test of the SiC / SiC composite material prepared in this comparative example showed that the room temperature fracture toughness was 17.6 MPa·m 0.5 The room temperature flexural strength is 423MPa, and the creep life in an air environment of 1300℃ and 120MPa is 89h.
[0067] Comparative Example 4
[0068] ① Preparation of core-shell structure powder: A SiC layer is deposited on the surface of B4C powder by a chemical deposition process (chemical vapor deposition) to form a core-shell structure powder. The particle size of the B4C powder is 500nm and the thickness of the SiC layer is 250nm.
[0069] ② Core-shell structure powder dispersion: The core-shell structure powder obtained in step ① is uniformly dispersed in an ammonium polyacrylate dispersant to obtain a modified liquid, wherein the volume fraction of the ammonium polyacrylate dispersant in the modified liquid is 60 vol.%; the third-generation SiC fiber preform having a PyC interface layer (PyC interface layer with a thickness of 200 nm) is pressure-impregnated 6 times using the obtained modified liquid, and then subjected to high-temperature treatment at 500°C in an inert atmosphere (argon) for 1 hour to obtain a modified SiC fiber preform; wherein the pressure of each pressure impregnation is 0.3 MPa, and the time of each pressure impregnation is 10 min.
[0070] ③ Impregnation, curing and cracking: Use liquid polycarbosilane to carry out 3 rounds of impregnation, curing and cracking process on the modified SiC fiber preform obtained in step ②. In each round of impregnation, curing and cracking process, the impregnation adopted is vacuum impregnation, the vacuum pressure is 100 Pa, the vacuum impregnation time is 1 h, the curing temperature is 300 ° C, the curing time is 1 h, the curing pressure is 2 MPa, the cracking temperature is 1000 ° C, the cracking time is 1 h, and the cracking is carried out under an inert atmosphere (argon).
[0071] ④ High temperature sintering: The composite material after impregnation, curing and cracking in step ③ is subjected to high temperature sintering in an Ar (argon) atmosphere, the high temperature sintering temperature is 1300° C., and the high temperature sintering time is 1 hour to obtain a SiC / SiC composite material.
[0072] The performance test of the SiC / SiC composite material prepared in this comparative example showed that the room temperature fracture toughness was 15.3 MPa·m 0.5 The room temperature flexural strength is 392MPa, and the creep life in an air environment of 1300℃ and 120MPa is 83h.
[0073] Comparative Example 5
[0074] Comparative Example 5 is substantially the same as Example 1, except that:
[0075] ① Preparation of core-shell structure powder: A B4C layer is deposited on the surface of SiC powder by chemical deposition process (chemical vapor deposition method) to form a core-shell structure powder. The particle size of SiC powder is 500nm and the thickness of B4C layer is 250nm. The core-shell structure powder is bombarded by argon ions in a vacuum environment. During the bombardment, the vacuum pressure is 10 -7 mbar, the voltage during the bombardment was 1.5 keV, the current was 6 mA, and the duration was 10 min, and the bombarded core-shell structure powder was obtained.
[0076] The performance test of the SiC / SiC composite material prepared in this comparative example showed that the room temperature fracture toughness was 15.5 MPa·m 0.5 The room temperature flexural strength is 395MPa, and the creep life in an air environment of 1300℃ and 120MPa reaches 84h.
[0077] Comparative Example 6
[0078] ① B4C powder dispersion: B4C powder (particle size of 500nm) is uniformly dispersed in ammonium polyacrylate dispersant to obtain a modified liquid, wherein the volume fraction of the ammonium polyacrylate dispersant in the modified liquid is 60vol.%; the obtained modified liquid is used to perform 6 pressure impregnations on a third-generation SiC fiber preform having a PyC interface layer (PyC interface layer with a thickness of 200nm), and then high-temperature treatment is performed at 500℃ in an inert atmosphere (argon) for 1h to obtain a modified SiC fiber preform; wherein the pressure of each pressure impregnation is 0.3MPa, and the time of each pressure impregnation is 10min.
[0079] ② Impregnation, curing and cracking: Use liquid polycarbosilane to carry out 3 rounds of impregnation, curing and cracking process on the modified SiC fiber preform obtained in step ①. In each round of impregnation, curing and cracking process, the impregnation adopted is vacuum impregnation, the vacuum pressure is 100 Pa, the vacuum impregnation time is 1 h, the curing temperature is 300 ° C, the curing time is 1 h, the curing pressure is 2 MPa, the cracking temperature is 1000 ° C, the cracking time is 1 h, and the cracking is carried out under an inert atmosphere (argon).
[0080] ③ High temperature sintering: The composite material after impregnation, curing and cracking in step ② is subjected to high temperature sintering in an Ar (argon) atmosphere, the high temperature sintering temperature is 1300° C., and the high temperature sintering time is 1 hour to obtain a SiC / SiC composite material.
[0081] The performance test of the SiC / SiC composite material prepared in this comparative example showed that the room temperature fracture toughness was 14.6 MPa·m 0.5 The room temperature flexural strength is 380MPa, and the creep life in an air environment of 1300℃ and 120MPa reaches 76h.
[0082] Comparative Example 7
[0083] ① SiC powder dispersion: SiC powder (particle size of 500 nm) is uniformly dispersed in ammonium polyacrylate dispersant to obtain a modified liquid, wherein the volume fraction of the ammonium polyacrylate dispersant in the modified liquid is 60 vol.%; the third-generation SiC fiber preform having a PyC interface layer (PyC interface layer with a thickness of 200 nm) is pressure-impregnated 6 times using the obtained modified liquid, and then subjected to high-temperature treatment at 500°C in an inert atmosphere (argon) for 1 hour to obtain a modified SiC fiber preform; wherein the pressure of each pressure impregnation is 0.3 MPa, and the time of each pressure impregnation is 10 min.
[0084] ② Impregnation, curing and cracking: Use liquid polycarbosilane to carry out 3 rounds of impregnation, curing and cracking process on the modified SiC fiber preform obtained in step ①. In each round of impregnation, curing and cracking process, the impregnation adopted is vacuum impregnation, the vacuum pressure is 100 Pa, the vacuum impregnation time is 1 h, the curing temperature is 300 ° C, the curing time is 1 h, the curing pressure is 2 MPa, the cracking temperature is 1000 ° C, the cracking time is 1 h, and the cracking is carried out under an inert atmosphere (argon).
[0085] ③ High temperature sintering: The composite material after impregnation, curing and cracking in step ② is subjected to high temperature sintering in an Ar (argon) atmosphere, the high temperature sintering temperature is 1300° C., and the high temperature sintering time is 1 hour to obtain a SiC / SiC composite material.
[0086] The performance test of the SiC / SiC composite material prepared in this comparative example showed that the room temperature fracture toughness was 15.0 MPa·m 0.5 The room temperature flexural strength is 388MPa, and the creep life in an air environment of 1300℃ and 120MPa reaches 79h.
[0087] Table 1: Performance test results of the materials finally prepared in each embodiment and each comparative example.
[0088]
[0089] Parts of the present invention that are not described in detail are well known to those skilled in the art.
[0090] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a matrix-modified SiC / SiC composite material, characterized in that: The method comprises the following steps: (1) depositing a SiC layer on the surface of B4C powder by chemical vapor deposition to obtain a core-shell structure powder; (2) bombarding the core-shell structure powder with argon ions under a vacuum environment, and then adding the bombarded core-shell structure powder into an ammonium polyacrylate dispersant to disperse it evenly to obtain a modified liquid; (3) using a modified liquid to perform multiple pressure impregnations on the SiC fiber preform having the interface layer, and then subjecting the preform to high temperature treatment to obtain a modified SiC fiber preform; (4) The modified SiC fiber preform is subjected to multiple rounds of impregnation, curing and cracking with a liquid polycarbosilane precursor, and then subjected to high-temperature sintering in an inert atmosphere to obtain a matrix-modified SiC / SiC composite material.
2. The preparation method according to claim 1, characterized in that: The particle size of the B4C powder is 500nm-1μm, and the thickness of the SiC layer is 250nm-500nm.
3. The preparation method according to claim 1, characterized in that: When bombarded by argon ions in a vacuum environment, the vacuum pressure is 10 -5 mbar, the voltage during the bombardment process is 1.0-2.0 keV, the current is 3-9 mA, and the bombardment time is 5-15 min.
4. The preparation method according to claim 1, characterized in that: The volume fraction of the ammonium polyacrylate dispersant in the modified liquid is 50-70 vol.%.
5. The preparation method according to claim 1, characterized in that: In step (3), pressure impregnation is performed 5 to 10 times; Preferably, the pressure of each pressure impregnation is 0.1-0.5 MPa, and the time of each pressure impregnation is 5-10 min.
6. The preparation method according to claim 1, characterized in that: In step (3), the temperature of the high temperature treatment is 400-600° C., preferably 500° C., and the time of the high temperature treatment is 0.5-2 h.
7. The preparation method according to claim 1, characterized in that: In step (4), 2 to 6 rounds of impregnation, curing and cracking are performed; During each round of impregnation, curing and cracking, the impregnation is vacuum impregnation, the pressure of the vacuum impregnation is 100-500 Pa, the time of the vacuum impregnation is 0.5-2 hours, the temperature of the curing is 200-400° C., the time of the curing is 0.5-1 hour, the temperature of the cracking is 900-1200° C., and the time of the cracking is 1-2 hours.
8. The preparation method according to claim 1, characterized in that: The temperature of the high temperature sintering is 1200-1400° C., preferably 1300° C., and the time of the high temperature sintering is 0.5-1.5 h.
9. The preparation method according to claim 1, characterized in that: The SiC fiber preform with an interface layer is a SiC fiber preform with a PyC interface layer.
10. A matrix-modified SiC / SiC composite material obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Core-shell structure ceramic powder, thermal insulation material and preparation method thereof
CN115433013A
Preparation method of ultrahigh-temperature ceramic modified SiC / SiC composite material
CN115650752A
Flowable fiber composite materials and methods of making and using the same
US20240246865A1